2022
DOI: 10.1186/s13063-022-06700-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of 5% lidocaine patches for postoperative pain management in patients undergoing unilateral inguinal hernia repair: study protocol for a prospective, double-blind, randomized, controlled clinical trial

Abstract: Background Acute postoperative pain is a common complication of inguinal hernia repair. Pain management using local application of anesthetic agents over the skin surrounding the surgical incision may reduce the requirement for other pain medications. Targeted topical analgesics such as 5% lidocaine patches have been known to improve acute and chronic pain. However, the clinical effect of lidocaine patches on postoperative pain after inguinal hernia repair has not been studied, especially in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…To address this, the current study compared the effectiveness of using triamcinolone acetonide along with lidocaine versus lidocaine alone for chronic pain after Lichtenstein repair. Lidocaine, a local anesthetic, blocks nerve signals and provides analgesia, while triamcinolone acetonide, a corticosteroid, reduces inflammation at the surgical site 5,14,17,18 . The current study findings showed that patients receiving triamcinolone acetonide with lidocaine experienced significantly lower chronic pain at different time points compared to those who received lidocaine alone, suggesting that this intervention consistently reduced postoperative pain at 1st week, 1st month, and 3rd month.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To address this, the current study compared the effectiveness of using triamcinolone acetonide along with lidocaine versus lidocaine alone for chronic pain after Lichtenstein repair. Lidocaine, a local anesthetic, blocks nerve signals and provides analgesia, while triamcinolone acetonide, a corticosteroid, reduces inflammation at the surgical site 5,14,17,18 . The current study findings showed that patients receiving triamcinolone acetonide with lidocaine experienced significantly lower chronic pain at different time points compared to those who received lidocaine alone, suggesting that this intervention consistently reduced postoperative pain at 1st week, 1st month, and 3rd month.…”
Section: Discussionmentioning
confidence: 99%
“…Although chronic pain following inguinal hernia repair has been thoroughly researched, the treatment remains difficult 1,5,6 . Almost 8% to 16% of patients report chronic pain within six months of hernioplasty, that significantly associated with quality of life 7 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations